Rural-urban disparity in knowledge and compliance with traffic signs among young commercial motorcyclists in selected local government areas in Oyo State, Nigeria. Issue 2 (3rd April 2017) - Olumide, Adesola O.; Owoaje, Eme T.
Abstract : This study compared knowledge and compliance with traffic signs among young commercial motorcyclists in rural and urban communities in Oyo state, Nigeria. Information on knowledge and compliance with 10 common traffic signs was obtained from 149 rural and 113 urban commercial motorcyclists aged 18–35 years. Aggregate knowledge scores were computed and categorized as good (≥5) and poor (<5) knowledge. Overall, 98.7% rural versus 61.1% urban motorcyclists had poor knowledge of traffic signs ( p < 0.05). After controlling for age, level of education and years of commercial riding, motorcyclists in the rural areas were more likely to have poor knowledge of the traffic signs (OR = 58.15; 95% CI = 11.96–282.79). A higher proportion of rural than urban motorcyclists never obeyed any of the traffic signs. Young rural commercial motorcyclists' knowledge and compliance with the road signs was poorer than their urban counterparts. Interventions to improve the rural motorcyclists' knowledge and ultimately compliance with road signs are urgently required.